T5 MicroRNA-140–5p Regulates Disease Phenotype in Experimental Pulmonary Arterial Hypertension via SMURF1. (12th November 2015) - Rothman, AMK; Arnold, ND; Pickworth, JA; Iremonger, J; Ciuclan, L; Allen, R; Guth-Gundel, S; Southwood, M; Morrell, NW; Francis, SE; Rowlands, DJ; Lawrie, A
Abstract : Introduction and objectives: Clinical therapies for the treatment of pulmonary arterial hypertension (PAH) target vasoconstriction. However, the proliferative pulmonary vascular remodelling that drives disease persists contributing to significant patient morbidity and mortality. MicroRNA (miR) are short non-coding RNA that mediate post-transcriptional regulation of mRNA targets. We hypothesise that dysregulation of miR leads to de-repression of cellular targets central to disease pathogenesis. We sought to identify dysregulated circulating miR in patients with PAH, determine their phenotypic effect using in vitro and in vivo models and identify key mechanistic regulators that may represent novel therapeutic targets. Methods: Two patient cohorts were used to identify and validate differential expression of miR in whole blood by microarray and single assay qPCR. Binding site and network analysis was used to identify key miR targets. Effect of miR on identified targets and disease phenotype was determined in pulmonary artery smooth muscle cells (PASMC) and in the monocrotaline (MCT) and Sugen5416 plus Hypoxia (SuHx) models of PAH. Results: Expression of miR-140–5p was reduced in whole blood samples from patients with PAH and experimental models of PAH. Network and pathway analysis identified key regulators of TGFß and PDGF signalling as miR-140–5p targets. Transfection with miR-140–5p inhibitor resulted in increased proliferation and migration of PASMC and de-repression of key targets. Nebulised delivery of miR-140–5p mimic prevented the development of PAH in the MCT rat model and attenuated progression of established PAH in MCT and SuHx rat models. In experimental models levels of SMURF1 protein correlated inversely with miR-140–5p. Direct regulation of SMURF1 by miR-140–5p was demonstrated in vitro by 3'UTR luciferase activity. Both miR-140–5p mimic and SMURF1 siRNA increased BMP response element activity identifying SMURF1 as a key negative regulator of BMP signalling in PASMC. Genetic ablation of SMURF1 in C57BL6 mice conferred allele dependent protection from SuHx induced PAH. Finally, whole blood mRNA and pulmonary vascular immunoreactivity of SMURF1 was increased in patients with PAH. Conclusions: These studies suggest that miR-140–5p and SMURF1 are key regulators of BMP signalling and disease pathology in PAH and highlight SMURF1 as a potential novel therapeutic target.